1983
DOI: 10.1107/s0108768183002633
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high hydrostatic pressure on the crystal structure of BaFCl in the pressure range up to 6.5 GPa

Abstract: High-pressure X-ray diffraction measurements were made with BaFC1 single crystals (space group P4/nmm) using a diamond-anvil cell on a four-circle diffractometer (six data sets, 30 to 50 reflections, R values ranging from 2.5 to 5.0%). This compound does not show a pressure-induced phase transition up to 6.5 GPa at ambient temperatures. At lower pressures the compressibility of the c axis is larger than that of the a axis. At 2 GPa the compressibility becomes isotropic and at higher pressures again anisotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 9 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Moreover, high-pressure research on PbClF-type materials has received tremendous interest owing to their quasi-2D layered structure, , which can provide an avenue for exploring pressure-induced layered to nonlayered structural phase transformations. Several high-pressure X-ray diffraction (HP-XRD) and theoretical studies were focused on understanding the high-pressure behavior of layered PbClF-type compounds. A HP-XRD study on MClF (M = Ca, Sr, Ba) and BaFBr compounds using a diamond anvil cell and synchrotron radiation revealed that CaClF and SrClF are stable up to 27 and 42 GPa, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high-pressure research on PbClF-type materials has received tremendous interest owing to their quasi-2D layered structure, , which can provide an avenue for exploring pressure-induced layered to nonlayered structural phase transformations. Several high-pressure X-ray diffraction (HP-XRD) and theoretical studies were focused on understanding the high-pressure behavior of layered PbClF-type compounds. A HP-XRD study on MClF (M = Ca, Sr, Ba) and BaFBr compounds using a diamond anvil cell and synchrotron radiation revealed that CaClF and SrClF are stable up to 27 and 42 GPa, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, extensive studies have been devoted to understand the high pressure behavior of PbClF-type materials. High pressure X-ray diffraction measurements on BaClF single crystals reveal that BaClF is stable up to 6.5 GPa, it has isotropic compressibility at 2 GPa, and later it becomes anisotropic . Subramanian et al determined the structural stability of BaClF up to 35 GPa, and they observed a monoclinic ( P 2 1 / m ) phase at around 22 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…High pressure X-ray diffraction measurements on BaClF single crystals reveal that BaClF is stable up to 6.5 GPa, it has isotropic compressibility at 2 GPa, and later it becomes anisotropic. 9 Subramanian et al 10 determined the structural stability of BaClF up to 35 GPa, and they observed a monoclinic (P2 1 /m) phase at around 22 GPa. Later, high pressure X-ray diffraction measurements 11,12 on MClF (M = Ca, Sr, Ba) and BaBrF compounds reveal that BaClF and BaBrF undergo structural phase transitions at 21 and 27 GPa, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…11,12 Finally, there have been a number of studies of the structural, vibrational, and high-pressure properties of these materials. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] They show anisotropic compressibilities and interesting composition dependent phase transitions, including a transition to a monoclinic (P 2 1 /m) phase in BaClF at 22 GPa. Returning to the response to ionizing radiation, the behavior of these halofluorides is in sharp contrast to apparently closely related materials, such as BaF 2 and BaIBr.…”
Section: Introductionmentioning
confidence: 99%